Design of CF for Automotive Body Parts Based on Artificial Intelligent - Bastian Wibar, Momang; N. M. Zuki, N. M. (2014)
Checking Fixture (CF) design is an important element in the stamping process of automotive parts and plays an integral role in linking Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM). In order to enhance CF design quality and efficiency, this paper proposes a portable quality-confirmation inspection device for automotive part. The concept of the computer-aided CF design includes a new volume bounding box generation approach for a gantry system framework. Embedded in the system, is a multi objective optimization algorithm which is used for locator layout design and a multi-surface extension and transition method for checking the surface quality.